Moving Target Network Defense Effectiveness Evaluation Based on Change-Point Detection. (14th June 2016) - Lei, Cheng; Ma, Duo-he; Zhang, Hong-qi; Wang, Li-ming
Abstract : In order to evaluate the effectiveness of moving target network defense, a dynamic effectiveness evaluation approach based on change-point detection is presented. Firstly, the concept of multilayer network resource graph is defined, which helps establish the relationship between the change of resource vulnerability and the transfer of network node state. Secondly, a change-point detection and standardized measurement algorithm is proposed. Consequently, it improves the efficiency of evaluation by measuring the change-point dynamically and enhancing the accuracy of evaluation based on multilayer network resource graph. What's more, in order to evaluate the defense effectiveness comprehensively, defense cost and benefits are set as evaluation indicators. Finally, experimental analysis, represented by MT6D and DNAT, proves the feasibility of the proposed evaluation method and the accuracy of the evaluation results.